Time delay control of cable-driven manipulators with adaptive fractional-order nonsingular terminal sliding mode. (July 2018) - Wang, Yaoyao; Yan, Fei; Jiang, Surong; Chen, Bai
Highlights: Propose a novel TDE-based adaptive FONTSM (AFONTSM) control scheme. Prove the stability of the closed-loop adaptive control system. Deduce the theoretical control error values. Verify the advantages of proposed control scheme with both simulations and experiments. Abstract: For the high performance control of cable-driven manipulators, a novel time delay control (TDC) scheme with adaptive fractional-order nonsingular terminal sliding mode (AFONTSM) is presented and studied in this work. The presented control scheme uses time delay estimation (TDE) as its basic framework, which can effectively obtain a fascinating model-free feature just using the time-delayed information of the closed-loop control system. Afterwards, a novel AFONTSM control scheme is applied to provide with good comprehensive performance under complicated lumped disturbance in both reaching and sliding phases. The presented control method can be easily applied in real situations thanks to TDE, meanwhile satisfactory control performance can be guaranteed benefiting from the adopted AFONTSM error dynamics. Stability analysis is given based on Lyapunov stability theory. Finally, the effectiveness and superiorities of our newly designed control scheme are validated through 2-DOFs (degree of freedoms) comparative simulations and experiments.